METODE MENGHAFAL NADZOM CEPAT : (Studi di Pondok Pesantren Lirboyo, Kediri) - Bahrul Ulum (LP3M IAI Al-Qolam Malang, 2021)
Pondok Pesantren salaf until now consistently used memorizing technique to learn Nadzom. This technique becomes one of learning methods for santri. Memorizing Nadzom certainly need particular method in order to let santri or students frequently mastering the Nadzom in certain time. At this stage, memorizing technique intensively can be primary reference. But, before applying this technique to the students, teachers shall start it with proper preparation. One of those preparation can be let the student absorb the motivation that memorizing is an easy task. Memorizing the Nadzom is one of steps should be fulfilled by santri to learn about Arabic grammatical language. Because within those Nadzom, the key words of grammatical lie on. Key words: memorizing technique, Nadzom, learning method, santri, pesantren.